PERANAN BALANCED SCORECARD (BSC) DALAM MENGHADAPI PERUBAHAN LINGKUNGAN BISNIS - Tho, Ivony (potensio, 2009)
The main goal of performance assessment is to motivateemployees in achieving Company’s goal and to obey the behavioralstandard in order to produce actions and resultsneeded. The performance assessment system chosen bycompany, in general, is only related to financial perspective.In this globalization era recently, financial benchmark is nolonger appropriate to asses Company’s performance becauseof their lack of information. Based on BalanceScorecard approach, the executive financial performancemust reflect the performance in satisfying the customerneeds, productive internal business process and cost effective,with/out the development of productive and committedemployees. Further, Balance Scorecard will analyze throughthose four key areas to assist traditional accounting assessmentin order to evaluate the successful of the company anddetermine the company’s direction. The perspective areaswhich include in Balance Scorecard are financial, customersatisfaction, internal business process and learning and development.The Balance Scorecard combination of the fourperspectives mentioned above, will assist the managers inorder to distinguish all relations which drive to the developmentof decision making and problem solving in the company.Key word: balanced scorecard, performance